The black/white academic achievement gap and Mocombe's Reading Room Series curriculum - Mocombe, Paul C. (Cambridge Scholars Publishing, 2020)
This work explores the concept of structural reproduction and differentiation through the origins of, and basis for, Paul C. Mocombe's Mocombeian Strategy (2005) and Reading Room Curriculum, published as Mocombe's Reading Room Series (2007). It highlights how black American practical consciousness and the academic achievement gap are a product of capitalist forces, relations of production, and their ideological apparatuses. As such, it is argued here that, to resolve the gap, black Americans should be treated as immigrant students against their structurally differentiated identities.